TEMPLE ART OF ODISHA: A STUDY OF THE DIVINE AND SEMI-DIVINE HUMAN FIGURES - Mohanandia, Ujwala Kumar; Nanda, Swetalina (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Divine beings are sacred, holy, or godly, and therefore transcend human boundaries. They have ultimate power, authority, and control. Divine beings are worshipped as gods and goddesses. The depiction of divine being is canonical, and breaking the law is banal. Semi-divine refers to something or someone who possesses a partial or mixed divine essence. In mythology, semi-divine refers to demigods or heroes who are the offspring of gods or gifted individuals. Semi-divine images play an important role in communicating spiritual and philosophical ideas in Odishan temple art. Images of demigods, heroes, and mythical figures, such as Yaksa, Kinnara, Gandharva, Apsara, Naga/Nagi, and Gana, are considered semi-divine. Semi-dines are revered as the guardians and protectors of the temple and its believers from risks. These figures are frequently used as decorative motifs, covering the temples’ walls and pillars to enhance their aesthetic appeal. The temples’ holy and semi-divine icons serve as visual representations of spiritual and philosophical ideas, inspiring devotion, contemplation, and artistic expression. Understanding these notions will help one better understand the symbols, motifs, and tales found in diverse creative works. Such images are frequently incorporate regional artistic styles, materials, and techniques, demonstrating the breadth of Indian art and culture.